STRATEGI GELAR KEKUATAN TNI ANGKATAN LAUT DALAM MENGATASI PELANGGARAN DI WILAYAH ALUR LAUT KEPULAUAN INDONESIA II GUNA MEWUJUDKAN STABILITAS KEAMANAN PERAIRAN DALAM RANGKA MENDUKUNG OPERASI MILITER SELAIN PERANG (OMSP) - Lukman Kharish; Ikhwan Syahtaria; Dohar Sianturi; Lukman Yudho Prakoso; Herlina Juni Risma Saragih; Ernalem Bangun (Sekolah Tinggi Pariwisata Mataram, 2022)
Security in the territorial waters of a country is one of the important elements in maintaining the sovereignty of a country which based on facts on the ground shows that the ALKI II region poses a threat to international shipping where the threats are in the form of smuggling of goods, human trafficking, as well as terrorism and the impact of Malaysia's expansionary politics. is the impact of the non-optimal security in the ALKI II area due to the non-optimal degree of TNI al strength and regulations that are still overlapping in overcoming violations in the ALKI II area, so this study aims to find out how the interoperability between TNI dimensions in the ALKI II area in supporting the sovereignty of the Republic of Indonesia. And how are the efforts in strengthening the strategy of the pattern of operations and deployment of TNI AL forces in the ALKI II region. Then this study uses a qualitative approach with descriptive analysis methods supported by literature studies as a method of data and fact tracking, where based on the results of the study it is known that interoperability between dimensions The TNI in the ALKI II area has not been well integrated and is still running independently and the pattern of operations and deployment of the TNI's combat force is not optimal yet with a centralized and regional nature so that optimization is needed. realizing the stability and security of Indonesian marine waters.